Peran Efikasi Diri dalam Keputusan Karier terhadap Hubungan antara Future Work Self dengan Adaptabilitas Karier pada Mahasiswa Tingkat Akhir - Nabilah, Arifiana; Indianti, Wahyu (Jurnal Psikologi Teori dan Terapan, 2019)
Competition in the current era of globalization requires individuals to be more adaptive in their careers. Career adaptability is one of the constructs related to career psychology that focuses on helping individuals to monitor career development during their lifetime. This research was conducted on 440 final year college students who were at least in the seventh semester of their studies at university. This study assumes that career decision self-efficacy a mediator for the relation between future work self and career adaptability. The results show that future work self has a strong relationship with career adaptability. The relationship is proved to be mediated partially by career decision self-efficacy. There are still other possible variables that can fully explain the relationship of future work self and career adaptability to final years college students.Keywords: Â Career adaptability, future work self, career decision self-efficacy, college students